Analysis of the Effectiveness of the Implementation of Crew Management System (CMS) on Monitoring of LNG Ship Crew Documents at PT. X - Kinanti, Anindya Fatika; Bugi Nugraha; Dyah Ratnaningsih; Intan Sianturi (Politeknik Ilmu Pelayaran Semarang, 2025)
Crew Management System (CMS) is a management system at PT. X, especially in monitoring documents for the crew of the Tangguh Foja LNG ship. Implementation of Crew Management System (CMS) at PT. X has several obstacles in connection with the effectiveness of document monitoring activities that hamper the smoothness of the management of crew documents, especially for preparation for the debriefing crew. The aim of this research is to determine the application, role and analysis of the effectiveness of the Crew Management System (CMS) system in relation to the implementation of monitoring crew documents at PT. X. This research method uses a qualitative method with a qualitative descriptive approach through case studies. Research data collection was carried out through interview techniques, field observations, documentation and identification of documents related to research. The results of research data as primary data were obtained from sources and field data from land practice locations at companies or PT. X, and secondary data in the form of documentation. The results of the research show that the Crew Management System (CMS) has a big influence for monitoring ship crew documents. However, the effectiveness of implementing the system for monitoring crew documents is quite effective, but there are factors or obstacles to the effectiveness of implementing monitoring of ship crew documents at PT. X.